Students Characterization from their Potential and Academic Talent in Antofagasta, Chile - García Cepero, Maria Caridad (Pontificia Universidad Javeriana, 2012)
The current situation of coverage, quality, equity and diversity in educational policies pose new challenges to educational institutions, especially the public ones, which must develop strategies to meet the needs of students who are in their classrooms capitalizing their strengths. With an exploratory research and a mixed explicative research methodology, we present the results the first phase of this study, corresponding to institutional educational projects analysis and characterization of outstanding students. We analyzed the results of 1,536 students from 18 educational institutions from Antofagasta and Calama (Chile). From the analysis and according to indicators of academic talent, the sample was characterized in four groups of students: outstanding, sub-nominated, over-constrained, and average. The sub-nominated student category raises questions concerning to the methodology for identifying talented and gifted students in Chilean programs, strongly grounded in teacher nomination. These findings note the need to generate alternative routes, such as self-nomination. To conclude, we give some suggestions on public policy regarding education for outstanding students in Chile. However these can be largely transferred to other cases throughout Ibero-America.